An exogenous cytokinin supply in the ornamental fern Asplenium nidus L. induces an unusual post-transplant biomass accumulation - Alberto Pagani; Danilo Carnelos; Jorge Molinari; Ernesto Giardina; Adalberto Di Benedetto (Ornamental Horticulture, 2021)
Ferns are ornamental plants with a low relative growth rate and long production cycles, which are grown at small pot volumes to optimize the commercial space for sale. However, the root restriction effects under this plant management can limit biomass accumulation and frond area. Since an exogenous spray with cytokinin (6-benzyl aminopurine (BAP)) has been suggested as a tool to override the root restriction in plants grown in pots, this study aimed to evaluate the effect of different BAP doses (5, 50, 100 or 200 mg L-1) once (7 days after transplant), twice (7 and 30 days after transplant) or three times (7, 30, and 60 days after transplant), on plant growth and frond area development in spore-propagated Asplenium nidus fern plants grown in pots. Both increasing the BAP doses and number of applications led to an unusual response: an excessive decrease in the frond plastochron and a significant increase in the frond number initiated at the apical shoot meristem. This large frond number was not sustained due to the low net photosynthetic rate of the younger fronds and significantly limited outward appearance.